Hubungan Pengetahuan tentang Jamban Sehat dan Lingkungan Fisik dengan Perilaku Buang Air Besar Sembarangan - Agustyaningsih, Titik; Kurnia, Anggraini Dwi; Larasati, Retno Yunita (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
There are 24.03% of Indonesia's population having open defecation behavior. This behavior has thepotential to cause a disease such as water-borne diseases. The research aims to determine the relationshipbetween knowledge about healthy latrines and physical environment with open defecation behavior. Thisresearch used quantitative descriptive method with cross sectional study approach. The number ofrespondents was 78 people using the quota sampling technique. Data analysis used the Spearman rankcorrelation test. The results showed that most respondents were 51 - 60 (37%), men (76%), farm laborers(73%), graduated from elementary school (64%), and had monthly income of less than Rp. 1,000,000.Significant relationship between knowledge about healthy latrines with BABS behavior with a value ofP=0,000, has a strong relationship with the value of r=-0,543, a significant relationship between physicalenvironment with BABS behavior with a value of P=0,000 has a strong level with a value of r=-0,712.Knowledge about healthy latrines and a good environment should be improved to reduce the behavior ofopen defecation in society.